1997
DOI: 10.1007/bf02737759
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone as an adjunctive treatment of bacterial meningitis

Abstract: This study was conducted on 77 Libyan infants and children aged month to 10 years with acute bacterial meningitis. Upon admission, the patients were divided randomly in two groups. Group I (38 patients) received ceftriaxone plus dexamethasone i.v. Group II (39 patients) received ceftriaxone alone. Both groups were compared for mean changes in CSF sugar, CSF protein and CSF polymorph count at 4th day of treatment. There was a significant difference between the two groups in CSF sugar and protein changes (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…reported no effect of dexamethasone (any neurological deficit at 3 or 6 months, 10 vs. 8%; any auditory deficit, 7 vs. 21%). Three studies from Pakistan, Libya, and India, respectively, reported no consistent effect on mortality, neurological (27 vs. 24%, 13 vs. 10%, and 21 vs. 13%, respectively), or auditory deficits (39 vs. 16%, no data, and 29 vs. 19%). Additionally, the study by Thomas et al.…”
Section: Early Randomised Studies (Table )mentioning
confidence: 98%
See 1 more Smart Citation
“…reported no effect of dexamethasone (any neurological deficit at 3 or 6 months, 10 vs. 8%; any auditory deficit, 7 vs. 21%). Three studies from Pakistan, Libya, and India, respectively, reported no consistent effect on mortality, neurological (27 vs. 24%, 13 vs. 10%, and 21 vs. 13%, respectively), or auditory deficits (39 vs. 16%, no data, and 29 vs. 19%). Additionally, the study by Thomas et al.…”
Section: Early Randomised Studies (Table )mentioning
confidence: 98%
“…The search resulted in 942 hits. From this search and from references in the studies identified by the search, 44 publications reporting clinical trials of relevance were identified, comprising 29 reports on randomised studies (in which group allocation is based on a non‐systematic, random allocation of patients, such as by a random sequence generation on a computer) . Of the publications reporting randomised studies, one included two studies, whereas three publications reported follow‐up data based on previously published trials.…”
Section: Search Strategymentioning
confidence: 99%
“…All the trials assessed glucocorticosteroids as add on therapy of standard care. The glucocorticosteroids included were hydrocortisone (8 trials) (27,42,43,(46)(47)(48)(49)(50); dexamethasone (15 trials) (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)43); and methylprednisolone (1 trial) (45) ( Table 1). 18 trials used placebo plus standard care (27-31, 33, 35-37, 40-43, 45, 46, 48, 49) and 6 trials used only standard care as control intervention (16,25,32,34,38,47).…”
Section: Included Trialsmentioning
confidence: 99%
“…The age groups of the randomized participants were infants (< 1 year) (38,43,44,47) and children (age > 1 year and < 12 years) (27-37, 39-42, 45, 47, 48). All the trials assessed glucocorticosteroids as add on therapy of standard care.…”
Section: Included Trialsmentioning
confidence: 99%